Antimicrobial activity and dye photodegradation of titanium dioxide nanoparticles immobilized on polyacrylonitrile-cellulose acetate polymer blended nanofibers. - Nkabinde, Sibongile Chrestina (Vaal University of Technology, 2019)
Electrospinning is a method that has gained more attention due to its capability in spinning a wide variety of polymeric fibers and nanoparticles embedded in polymer fibers. Polymer blending has been considered the most appropriate way for creating new materials with fused properties which improve poor chemical, mechanical, thermal and dynamic mechanical properties of each polymer. Hence, in this study, electrospinning technique was used to fabricate polyacrylonitrile (PAN) nanofibers at concentrations of (10, 12 and 14 wt%) and cellulose acetate (CA) nanofibers at concentrations of (14, 16 and 18 wt%). 10wt% of PAN and 16 wt% of CA were blended together and the optimum blend ratio was found to be 80/20 PAN/CA. TiO2 nanoparticles (0.2 and 0.4 wt%) were incorporated into CA nanofibers and (1, 2 and 3 wt%) were incorporated into PAN and PAN/CA blended polymers, respectively. Applied voltages of 20, 22 and 24 kV were varied at a spinning distance of 15cm and the optimum voltage for the fabrication of composite was 22 kV. The sol-gel method was used to synthesise the TiO2 nanoparticles at different calcination temperatures of 400, 500 and 600 ºC. The fabricated composite nanofibers were tested for antibacterial and photocatalytic activities. The synthesised nanomaterials were characterized using SEM, TEM, EDX, UV-Vis, PL, FTIR spectroscopy, XRD and TGA. The absorption and emission spectra illustrated the formation of TiO2 nanoparticles and the increase in absorption band edges. TEM showed the spherical morphology of the nanoparticles with average diameter of 12.2 nm for nanoparticles calcined at 500 ºC. SEM illustrated the diameter and morphology of the nanofibers and composites with the average diameter of 220, 338, 181, 250, 538, 294 nm for PAN, CA, PAN-TiO2, CA-TiO2, PAN/CA and PAN/CA-TiO2, respectively. XRD revealed anatase phase as the dominant crystalline phase of the synthesised nanoparticles. FTIR spectroscopy and EDX signified that the formation of composite nanofibers and the presence of TiO2 nanoparticles corresponded to the Ti-O stretching and Ti-O-Ti bands on the FTIR spectra. The antimicrobial activity of the composite nanofibers were tested against E. coli, S. aureus and C. albicans microorganisms. The photocatalytic activity of the nanomaterials was tested using methyl orange dye. PAN/CA-TiO2 composite nanofibers revealed the greatest antibacterial activity against selected microorganisms as compared to the other nanocomposites. PAN/CA-TiO2 nanocomposite (44%) showed greater rate of photodegradation of methyl orange than PAN-TiO2 nanofibers (28%) and TiO2 nanoparticles (12%) under visible light irradiation.
M. Tech. (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Antimicrobial activity; Dye photodegradation; Titanium dioxide; Nanoparticles; Nanofibers; Polyacrylonitrile-cellulose acetate polymer; Dissertations, Academic -- South Africa; Polymers; Nanoparticles; Electrospinning; Polyacrylonitrile -- Testing